Peningkatan Kemampuan Berpikir Kritis melalui Model Problem Based Learning Berbasis Literasi pada Pendidikan Pancasila Kelas V - damayanti, almira rahma; Aries Tika Damayani; Khusnul Fajriyah; Sri Wahyuningsih (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
Students' critical thinking skills still need to be improved because when asked to explain an issue, they tend to give short answers without explanation or underlying arguments. In addition, students also seem less enthusiastic about literacy. This research is a classroom action research conducted at SDN Sendangmulyo 02 Semarang with a focus on grade VB students. The purpose of this study is to improve students' critical thinking skills using a literacy-based PBL model in Pancasila Education lessons. This research was conducted in two cycles, each of which includes the planning, implementation, observation, and reflection stages. In this PTK, the data collection method used is a test. Data analysis shows that in the pre-cycle the percentage of critical thinking skills completion was 30%. In Cycle I, the percentage of critical thinking skills completion was 44%, which then increased to 78% in Cycle II. These findings indicate that the literacy-based PBL model can improve students' critical thinking skills in Pancasila lessons.